Meningkatkan Motivasi Baca Tulis Al-Qur’an Siswa melalui Media Audiovisual di MTs Al-Jihad Medan - Arlina, Arlina; Fehbrina, Novia; Ningsih, Setia; anggitasarihasibuan, putri; Sipahutar, Nurhasanah; Saif, Muhammad (Comit: Communication, Information and Technology Journal, 2024)
ABSTRACT Anak-anak MTs Al-Jihad Medan kelas VIII-1 tidak mau belajar membaca dan menulis, sehingga mereka kesulitan untuk membaca Alquran. Alat bantu audio-visual digunakan dalam penelitian ini untuk mengevaluasi apakah siswa termotivasi untuk belajar Alquran. Researchers use a mix of qualitative and quantitative techniques in their examinations of action research in the classroom. The Kemmis & Mc. model was employed in this study. Taggart, which consists of two cycles. Surveys, observations, interviews, and written data are used in this research. The results of this study show that the intervention put into place with the eighth grade and first year Muslim students at Al-Jihad Medan increased their motivation to learn the Koran using audiovisual media. Pre-cycle findings improved significantly in the second cycle, proving this to be the case. According to the data, 28 out of 43 students (or 65%) did not finish the course in the pre-cycle period, 18 out of 43 students (or 42%) did not finish the course in the first cycle, and 6 out of 43 students (or 14%) did not finish the course in the second cycle. When comparing the results from before the cycle to those after it, we find that, on average, students in MTs Al-Jihad Medan's eighth grade are 51% more motivated to read and write the Koran after being exposed to audiovisual materials. Keywords: Motivation, BTQ, Audio-Visual Media